Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Pegawai pada PT. Unggul Widya Teknologi Lestari - Anita Cemerlang; Anwar Ramli; Abdi Akbar Idris; Siti Hasbiah; Agung Widhi Kurniawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to determine the influence of motivation on employee performance; the influence of work discipline on employee performance; and the combined influence of motivation and work discipline on employee performance at PT. Unggul Widya Teknologi Lestari. The subjects of this study consist of 125 employees of PMKS Agri Baras at PT. Unggul Widya Teknologi Lestari. The data collection technique used was a questionnaire.